Study on Corporate Social Responsibility and Ombudsman’s Offices Complaints of banks, considering the size and type of control in Brazil - Alves, Carlos André de Melo; Machado Filho, Claudio Antonio Pinheiro; Lima, Gerlando Augusto Sampaio Franco de (Revista de Administração da UFSM, 2017)
In Brazil, the ombudsman’s offices in banks has the function to deal with customers and users ultimately. This article seeks to demonstrate the evolution of the issues related to the ombudsman’s offices complaints of banks, considering the size and type of control in Brazil. An exploratory research was carried out with a non-probabilistic sample of 26 public, domestic private and foreign banks. The data was collected from 1.377 complaints related to the ombudsman’s offices of these banks, ended from the 1st semester of 2008 to the 1st semester of 2011 and released by the Central Bank of Brazil. Data analysis employed descriptive statistics, inferential statistics and Multiple Correspondence Analysis. It was ascertained that the complaint issue ’Ombudsman’ predominated in the complaints occurrences until the 1st semester of 2009 while other complaint issues prevailed from the 2nd semester of 2009. The issues ’Term Breach’ and ’Others and Dial Direct Free’ were conditioned mostly to middle-size banks and domestic private ones, and ’Customer Service’ was associated mostly to very large banks that are public. Results can contribute to enhance the banks’ ombudsman’s offices regulatory duties, and also can contribute to understand the implementation of socially responsible actions of banks to meet both customers and users as banks’ stakeholders in Brazil.